1994
DOI: 10.3109/00207459408986076
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced hypnotizability by cerebrally applied magnetic fields depends upon the order of hemispheric presentation: An anistropic effect

Abstract: A significant alteration in the hypnotizability of normal subjects after brief (15 min) exposures to weak (1 microT) pulsed magnetic fields over the temporal lobes was determined by the serial order of hemispheric stimulation. Only subjects who received the right hemispheric stimulation first displayed significantly elevated hypnosis induction profile scores (effect size equivalent to a correlation of 0.41). Implications for a technology that can: a) modify hypnotizability, b) encourage the consolidation of qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Laidlaw (1993) assessed hypnotizability in a group of neurological patients who had suffered closed head injuries, but did not specifically consider laterality. Relatedly, Persinger and his colleagues (Healey et al, 1996; Tiller and Persinger, 1994) found that the brief application of a weak pulsed magnetic field over the right temporal lobe, inducing activity resembling complex partial epileptic-like seizures, increased hypnotizability in neurologically intact subjects. The present study sought to contribute to neuropsychological investigations of hypnosis by examining hypnotic susceptibility in patients with clearly lateralized brain damage secondary to stroke.…”
Section: Introductionmentioning
confidence: 99%
“…Laidlaw (1993) assessed hypnotizability in a group of neurological patients who had suffered closed head injuries, but did not specifically consider laterality. Relatedly, Persinger and his colleagues (Healey et al, 1996; Tiller and Persinger, 1994) found that the brief application of a weak pulsed magnetic field over the right temporal lobe, inducing activity resembling complex partial epileptic-like seizures, increased hypnotizability in neurologically intact subjects. The present study sought to contribute to neuropsychological investigations of hypnosis by examining hypnotic susceptibility in patients with clearly lateralized brain damage secondary to stroke.…”
Section: Introductionmentioning
confidence: 99%
“…If weak MFs have an effect upon nociceptive processing, it may well be of interest to explore its use in novel analgesic processing, such as hypnotic or placebo analgesia, particularly since opiate antagonist naloxone has been shown to attenuate MF-induced analgesia [Thomas et al, 1997a,b] as well as placebo analgesia [Amanzio and Benedetti, 1999;Amanzio et al, 2001]. MFs could also be used to augment or supplement the induction of hypnotic analgesia, as some previous studies have suggested [Tiller et al, 1994;Healey et al, 1996].…”
Section: Analysis Of the Electroencephalogram (Eeg)mentioning
confidence: 99%
“…4824; E-mail: mpersinger@laurentian.ca ges in power within the right temporal-parietal and right frontal regions [7]. Preferential exposure over the right hemisphere has been associated with increased scores for hypnosis induction capacity or suggestibility [8,9]. This sensitivity of the right hemisphere to weak experimentally generated and natural geomagnetic fields has been reported frequently [10].…”
Section: Introductionmentioning
confidence: 98%